THE NUMERICAL MODEL OF 2G YBCO SUPERCONDUCTING TAPE IN THE WINDINGS OF THE TRANSFORMER - WOŹNIAK, Łukasz; SURDACKI, Paweł; JAROSZYŃSKI, Leszek (Applied Computer Science, 2017)
Computer assisted calculations consists in applying software for the simu-lation of models of certain devices and later analysing their behavior under given conditions corresponding to real working conditions in a specific environment.The paper proposes a circuit model of 2G YBCO super-conducting tape created in the PSpice program. The model consists of passive blocks and active user blocks of analogue behavioural modelling (ABM). ABM blocks calculate the conductances, the currents of the indi-vidual layers of the superconducting tape, its thermal capacity, the heating power, the cooling power and resulting temperature of the tape. The model uses table of thermal power density passed to the liquid nitrogen vs. temperature. Smooth transition of the YBCO superconductor layer into the resistive state is described by Rhyner’s power law. The developed model was used for generating waveforms of thermal and electrical quantities.